Preliminary Phytochemical Analysis And Antimicrobial Activty Of Andrographis Serphyllifolia- (Rottler ex Vahl) Wight: Acanthaceae - A, Vadivalagan; R, Kannan.; Balasubramaniam, V. (International Journal of Scientific Research in Biological Sciences, 2019)
Andrographis serpyllifolia (Rottler ex Vahl) Wight, belonging to Acanthaceae family known for its ethnobotanical importance and possess anti- venom potential especially for snake and scorpion bites. The present study is focused to evaluate the phytochemical profiles and antimicrobial activity A. serpyllifolia using petroleum ether, acetone and methanol solvents. The results revealed that presence of alkaloids, flavonoids, saponins, phenols, steroids, glycosides, tannins and resins in various extracts studied. Antibacterial activity of A. serpyllifolia against Gram negative bacterial strains Serratia marcescens and Escherichia coli showed 6 mm and 9 mm zone of inhibition respectively in 50% concentration of extracts studied. Antifungal activity of petroleum ether extract showed highest zone of inhibition (11 mm) against Penicillium notatum and Fusarium oxysporum at 100% concentration.